Information Technology and Time-Based Competition in Financial Markets - Dewan, Sanjeev; Mendelson, Haim (Management Science, 1998)
This paper studies time-based competition in imperfect securities markets, linking IT investment decisions, information processing delays, and trading strategies. At the IT investment stage, traders trade off the cost of IT against their anticipated trading profits. At the trading stage, each trader devises a trading strategy based on his new information while taking into account the impact of both his own trades and those of other traders in the market. Our results illustrate how traders react to market imperfections due to trading costs and information processing delays, and how superior traders convert a timeliness advantage into higher trading profits. They also shed light on the relationship between the price adjustment process and traders' information processing delays. Timeliness imposes an interesting structure on trader competition: traders with longer information processing delays trade less frequently, submit smaller orders and enjoy lower profits per trade. Our analysis of traders' IT investment decisions demonstrates how factors such as IT costs, number of traders, and the frequency and nature of new information affect the level of IT investments. We further illustrate how improved IT infrastructure translates into competitive advantage.